MANAJEMEN PENGELOLAAN PROGRAM TAHFIDZ AL-QUR’AN DENGAN METODE QIRO’ATI DI SD MIFTAHUSSA’ADAH GEBOG KUDUS - Mawardah, Riskiatul; Sri Utaminingsih; Khamdun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to determine how the Tahfidz Program Management at Miftahussa'adah Gebog Kudus Elementary School. Management can be interpreted as an activity that integrates educational resources to be centered in an effort to achieve predetermined educational goals. Management of the Tahfidz Program at Miftahussa'adah Gebog Kudus Elementary School is in accordance with the Management Standards at the Elementary School level according to Permendikbud Number 47 of 2023 which includes Planning, Implementation, and Supervision. This research uses a qualitative descriptive method with a case study approach. This data was obtained through observation, interviews, and documentation. The researchers used Miles and Huberman's theory, namely data reduction, data disclosure, conclusion drawing and validation. The results showed that the Management of the Tahfidz Program at Miftahussa'adah Elementary School has been carried out in accordance with management functions, namely planning, implementation, supervision. There are several supporting and inhibiting factors for the Tahfidz Al-Qur'an program at Miftahussa'adah Gebog Kudus Elementary School. Supporting factors include: Strong determination from oneself, Support from parents and teachers, Physical and psychological good students, and Learning environment / Comfortable facilities. While inhibiting factors include: students not participating in the Pre Tahfidz Program, students are less focused on learning the Qur'an using the Qiroati method, and school holidays.